2002
DOI: 10.1029/2002gl015884
|View full text |Cite
|
Sign up to set email alerts
|

Bathymetric effect on the winter sea surface temperature and climate of the Yellow and East China Seas

Abstract: Whether and how the atmosphere reacts to changes in extratropical sea surface temperature (SST) is under intense debate and this lack of understanding has been a major obstacle in the study of non‐El Nino climate variability. Using new satellite measurements, we detect clear ocean‐to‐atmospheric feedback in the Yellow and East China (YEC) Seas that is triggered by the submerged ocean bottom topography. Under intense surface cooling in winter, water properties are well mixed up to 100 m deep. Ocean depth thus h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
184
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(201 citation statements)
references
References 17 publications
12
184
1
Order By: Relevance
“…The area of the highest temperature is near the Kuroshio area in the East China Sea, where the isotherm is dense due to the strong Kuroshio. The above pattern of temperature in winter is consistent with the observed SST in Xie et al (2002). In summer, the temperature is low in the open sea and high in the coastal sea.…”
Section: Horizontal Distribution Of Circulation and Temperaturesupporting
confidence: 75%
See 1 more Smart Citation
“…The area of the highest temperature is near the Kuroshio area in the East China Sea, where the isotherm is dense due to the strong Kuroshio. The above pattern of temperature in winter is consistent with the observed SST in Xie et al (2002). In summer, the temperature is low in the open sea and high in the coastal sea.…”
Section: Horizontal Distribution Of Circulation and Temperaturesupporting
confidence: 75%
“…Positions and observed temperatures in the YS in July of , 2002from Liang (2005 are shown in Figs. 9, 10 and 11, from which one can see easily that the surface mixed layer of temperature lies in the YS in summer.…”
Section: Evaluation By Observationsmentioning
confidence: 99%
“…Increasing the SST resolution improved both the position and intensity of the storm when compared to observations. Similar cases have since been noted by Xie et al (2002) and Thiébaux et al (2003). Yamamoto and Hirose (2007) found that the use of eddy-resolving SST data improved the simulation of a storm in their case study, though interestingly this was attributed to unrealistically strong SST gradients in the optimum interpolation SSTs which lacked mesoscale ocean eddies.…”
Section: Introductionmentioning
confidence: 58%
“…In the case study of Xie et al (2002), increasing the SST resolution led to an increase in the intensity of the cyclone, so it is of interest to look for changes in growth rate and intensity of storms. Figure 6 shows distributions of the storm intensity and tendency in the Gulf Stream region shown in Fig.…”
Section: Storm Track Sensitivity To Sst Resolutionmentioning
confidence: 99%
“…In fact, Xie et al (2002) suggest that the SST increase over the Yellow and East China Sea shelves causes the low SLP, and that the resultant SLP field leads to the wind field adjustment as found in satellite observations. However, the relationship between the storm development and SST gradient across the Kuroshio front (Xie et al 2002) is unclear in the present analysis, presumably due to the relatively coarse grid in Fig. 4.…”
Section: Air-sea Interaction Over the East Asian Marginal Seasmentioning
confidence: 99%